Memahami Tiga Pilar Pembelajaran: Guru, Siswa, dan Materi Pembelajaran - Dellisa Ahyani; Elvara Salsabilla Chaisa; Fadilah; Sofyan Iskandar (STAI AL-AMIN, 2025)
This paper explores the essential roles of teachers, students, and learning materials as the three foundational pillars of effective learning. The objective of this study is to address the imbalance often found in educational practices that emphasize only one or two elements, neglecting the importance of their interconnectedness. Using a qualitative descriptive method and literature review approach, this paper analyzes how these three components function individually and collectively within contemporary educational settings. Teachers are examined as facilitators and agents of pedagogical design, students as active participants and co-constructors of knowledge, and learning materials as dynamic tools that support cognitive and skill development. The findings reveal that meaningful learning experiences emerge when there is a harmonious integration of teacher guidance, student engagement, and relevant instructional content. The study also highlights how the neglect of one pillar can hinder the learning process and reduce educational effectiveness. In conclusion, this paper emphasizes the need for a balanced, holistic approach in educational planning and instructional practice, ensuring that teachers, students, and materials work in synergy to enhance learning outcomes.